2007
DOI: 10.14236/jhi.v15i1.642
|View full text |Cite
|
Sign up to set email alerts
|

Investigating patients' and general practitioners' views of computerised decision support software for the assessment and management of cardiovascular risk

Abstract: Purpose This paper reports an evaluation of the usability and acceptability of a computer-based decision support program (EMPOWER TM ) for cardiovascular risk from the perspectives of both general practitioners (GPs) and consumers. Methods A qualitative research design utilised semi-structured telephone interviews to assess the program from participants' perspectives. Qualitative approaches included the use of purposeful sampling, the collection of open-ended data, and the analysis of text and personal interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…16 Some studies suggest less decisional conflict and improved satisfaction with decision making as a result. 8 Whether use of a decision aid impacts on the actual decisions made by patients is, however, less evident. 16 Assessment of patients' responsiveness to a decision support tool for primary prevention of CVDs has been investigated.…”
Section: Advantages For Patientsmentioning
confidence: 99%
See 4 more Smart Citations
“…16 Some studies suggest less decisional conflict and improved satisfaction with decision making as a result. 8 Whether use of a decision aid impacts on the actual decisions made by patients is, however, less evident. 16 Assessment of patients' responsiveness to a decision support tool for primary prevention of CVDs has been investigated.…”
Section: Advantages For Patientsmentioning
confidence: 99%
“…van Steenkiste and Wilson both found that decision support is welcomed by patients who enjoyed sharing information with a professional on a personal cardiovascular risk management plan. 8,17 Barriers to adoption…”
Section: Advantages For Patientsmentioning
confidence: 99%
See 3 more Smart Citations